2013
DOI: 10.1007/s12039-013-0496-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of phosphorus ylides 31: Reaction of azidocoumarin with active phosphonium ylides, synthesis and antitumour activities of chromenones

Abstract: The reaction of 4-azidochromen-2-one (1) with the nucleophilic phosphacumulene ylides 2, 8, and 12 afforded the new heterocyclic triazoles, triazepines, aziridine, pyrrolone containing a coumarin moiety. Cycloaddition reactions took place first to give triazoline 3 and 9. The triazolines rearranged to the triazepines 4, 10, and 13 accompanied by elimination of triphenylphosphine leading to the phosphorus-free triazepines 5, 11, and moreover, aziridine 6 was produced via nitrogen extrusion from the triazoline 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…Our continuing interest in the reactions of active phosphacumulene and phosphaallene (hexaphenylcarbodiphosphorane ylide) ylides to prepare carbocyclic and heterocyclic phosphorus compounds of biological interest, [26][27][28][29][30][31] led us to investigate and compare the behaviour of these phosphonium ylides with 4-aminoantipyrine (4-amino-1,5-dimethyl-2-phenyl-1,2dihydropyrazol-3-one-) (1), 4-amino-2-oxo-2H-chromene-3carbaldehyde (9), and 2-chloroquinoline-3-carbaldehyde (12) to synthesise new bioactive phosphorus compounds and their evaluation as antimicrobial agents.…”
Section: Resultsmentioning
confidence: 99%
“…Our continuing interest in the reactions of active phosphacumulene and phosphaallene (hexaphenylcarbodiphosphorane ylide) ylides to prepare carbocyclic and heterocyclic phosphorus compounds of biological interest, [26][27][28][29][30][31] led us to investigate and compare the behaviour of these phosphonium ylides with 4-aminoantipyrine (4-amino-1,5-dimethyl-2-phenyl-1,2dihydropyrazol-3-one-) (1), 4-amino-2-oxo-2H-chromene-3carbaldehyde (9), and 2-chloroquinoline-3-carbaldehyde (12) to synthesise new bioactive phosphorus compounds and their evaluation as antimicrobial agents.…”
Section: Resultsmentioning
confidence: 99%
“…Cycloaddition of azide 1 and thiophosphacumulene 12 gave the phosphanylidenetriazepane 11 , while elimination of triphenylphosphine resulted in triazepanone 12 (Scheme ). Moreover, the antitumor activity of these compounds was evaluated in vitro against the breast cancer cell line MCF‐7 and liver HPEG2 human solid tumor cell line (Scheme ) …”
Section: Discussionmentioning
confidence: 99%
“…Triazepanes are important seven‐membered heterocyclic ring compounds containing three nitrogen atoms. They and their derivatives possess various biological actives such as an antitumor, antimicrobial, antibacterial, and anticancer . In this review, based on the position of the nitrogen atoms in the final triazepine compounds, they are classified as TAP‐1,2,3, TAP‐1,2,4, TAP‐1,2,5, and TAP‐1,3,5, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the presence of an azo functionality in many compounds is essential for the exhibition of activity . In addition, the existence of phosphanylidene group also enhanced the biological activity . The present study is focused on the possibility of developing new heterocyclic containing phosphorus moieties with antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%